High Prevalence of Nutritional Risk Among Pulmonary Patients Living on the Tibetan Plateau - Quncuo, Chilie; Liang, Ying; Li, Qiuyu; She, Xiaoli; Cuo, Bian Ma; Qiongda, Bianba; ChuTso, Meilang; Sun, Yongchang (Frontiers in Nutrition, 2022)
Background: Nutritional risk is associated with adverse clinical outcomes and is more prevalent in pulmonology patients than in those admitted to other departments. High-altitude environments can affect patients with chronic respiratory diseases but that there is limited evidence of the prevalence of nutritional risk among hospitalized patients with respiratory diseases in high-altitude areas such as the Tibetan Plateau. This study aimed to investigate the nutritional risk and nutritional status of inpatients with different major respiratory diagnoses permanently living on the Tibetan Plateau (≥3000 m above sea level). Methods: In this cross-sectional study, we consecutively recruited inpatients admitted to the Department of Respiratory and Critical Care Medicine of the Tibet Autonomous Region People’s Hospital of Lhasa. between November 2020 and May 2021. We used the Nutrition Risk Screening (NRS) 2002 tool to assess nutritional risk in these patients. According to NRS-2002 scores, patients were divided into three groups (NRS-2002 0-2, 3-4, and ≥5). The differences in age, sex, major respiratory diagnoses, comorbidities, body mass index (BMI), and laboratory findings among the groups were analyzed. Results: A total of 289 eligible patients were enrolled in the study, and 46.1% (133/246) of them were at nutritional risk (NRS-2002 ≥3). Twenty-one (7.3%) patients were at high nutritional risk (NRS-2002 ≥5). The proportions of patients with nutritional risk (NRS-2002 ≥3) were relatively high among patients with lung cancer (58.8%), interstitial lung disease (58.3%), pulmonary embolism (52.9%), and tuberculosis (50.0%). Laboratory findings showed that patients with NRS-2002 scores of 3-4 and ≥ 5 had lower red blood cell counts and serum albumin and hemoglobin levels and higher C-reactive protein (CRP) levels than those with NRS-2002 scores <3. Conclusion: The prevalence of nutritional risk was high among pulmonology department inpatients permanently living on the Tibetan Plateau. Patients with lung cancer, interstitial lung disease, pulmonary embolism or tuberculosis were more likely than patients with other diagnoses to have nutritional risk. The nutritional risk of inpatients in respiratory department in plateau area should not be ignored, and patients with high nutritional risk should be intervened in time.